Hidden beauty of honeymoon beach: a potential attraction for tourists (a review of a tourism object) - Wajdi, Majid; Christiani, Rachel; Sari, Ni Gusti Ayu Komang Tri Purnama; Novitriana, Komang; Putri, Ni Putu Angelyani Sugiantari; Putri, Kadek Arisita Dhyana (Journal of Commerce, Management, and Tourism Studies, 2023)
Hidden beauty of Honeymoon Beach becomes a potential attraction for tourists, in this paper the purpose of choosing a Honeymoon Beach is because you want to review more deeply about the beach where it is hidden and rarely visited by tourists. It is important that we can preserve the natural beauty that is on the Honeymoon Beach so that the Honeymoon Beach is also known by many tourists and also the Honeymoon Beach can be managed as a tourist attraction like other beaches. The method used in this writing is a qualitative method, the author conducts research with observation, document analysis and focus group discussion. The type of data source obtained by the author is secondary data that comes from online media such as the internet in the form of news articles, photos, and others. Based on the results of data collection that has been carried out the result is about what are the important factors that cause this beach to have its own uniqueness. Among them are hidden beaches and coral caves which are the center of attention. Beside that the obstacles or challenges faced by the author in terms of location observation and also the weather where should this beach be paid more attention because the road access to this beach is still minimal and quite extreme so it needs more attention. So, the author wants to review more about the honeymoon beach considering its considerable potential to become a new tourist destination in Bali, especially in the Jimbaran area that deserves to be introduced to the public.